2000
DOI: 10.1161/01.hyp.36.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Patterns in Normal Pregnancy, Gestational Hypertension, and Preeclampsia

Abstract: Abstract-With the aim to describe the daily pattern of blood pressure during the trimesters of pregnancy in clinically healthy women as well as in pregnant women who developed gestational hypertension or preeclampsia, we analyzed 1494 blood pressure series systematically sampled by ambulatory monitoring for 48 hours every 4 weeks after the first obstetric visit in 124 women with uncomplicated pregnancies, 55 with gestational hypertension, and 23 with a final diagnosis of preeclampsia. The circadian pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 39 publications
12
110
1
9
Order By: Relevance
“…11,36,37 In the present study, the prevalence of sleep hypertension among 31 women with preeclampsia was 68%. Furthermore, we found that non-dippers and dippers with preeclampsia differ not only in their hemodynamic response during night, but also in their physiological response to darkness, as shown by the blunted nocturnal melatonin secretion in non-dippers.…”
Section: Discussionsupporting
confidence: 44%
“…11,36,37 In the present study, the prevalence of sleep hypertension among 31 women with preeclampsia was 68%. Furthermore, we found that non-dippers and dippers with preeclampsia differ not only in their hemodynamic response during night, but also in their physiological response to darkness, as shown by the blunted nocturnal melatonin secretion in non-dippers.…”
Section: Discussionsupporting
confidence: 44%
“…It is well recognized that a relatively large proportion of pregnant women may have masked gestational hypertension, undetected by office BP measurements, but revealed by specific BP index or circadian patterns computed with ambulatory BP monitoring. [31][32][33] Notably, pregnant women at increased risk of hypertension disorders tend to have higher night-time ambulatory BP than women without development of hypertension complications during pregnancy. 33 At the same time, night-time ambulatory BP is an independent predictor of LA size in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Notably, pregnant women at increased risk of hypertension disorders tend to have higher night-time ambulatory BP than women without development of hypertension complications during pregnancy. 33 At the same time, night-time ambulatory BP is an independent predictor of LA size in hypertensive patients. 34 In this context, the presence of an abnormal P wave at ECG in the early phase of gestation could be considered as a marker of high or high-normal BP values in women with normal BP detected in the office, and consequently refine the predicted risk of hypertensive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…During normal pregnancy, BP steadily decreases up to 21 weeks' gestation and then increases during the second half of pregnancy (14). Our assessment of hypertension during pregnancy probably only captured severe case subjects in whom BP remained elevated even during early pregnancy.…”
Section: Methodsmentioning
confidence: 99%